GEJALA KLINIS DAN PATOLOGI ANATOMI PASCA INFEKSI Campylobacter jejuni PADA AYAM BROILER [Clinical Symptoms and Pathology Anatomy due to Infection Campylobacter jejuni on Broilers] - Andriani, Andriani; Sudarwanto, Mirnawati; Setiyaningsih, Surachmi; Kusumaningrum, Harsi Dewantari; Pisestyani, Herwin (BERITA BIOLOGI, 2012)
Campylobacter spp. is a bacteria foodborne zoonotic agent that can infect humans and animals, especially birds. This bacteria can cause important problems in the public health since the beginning at the farm level, the level of retail and on the table. Poultry meat is the main source of contamination because the digestive tract of poultry is the predilection of Campylobacter jejuni. During this infection C. jejuni in poultry did not show typical clinical symptoms, making detection quite difficult to diagnose this disease at the farm level. Incidence infection of Campylobacter sp. in developed countries had 5-90%. Currently poultry production and consumption are predicted to still increase due to a high demand for low price protein. This research is conducted to determine the clinical and pathologic anatomy due to an infection of C. jejuni on chicken digestive tract. A total of 105-day-old chickens are divided into 3 groups, each consisting of 35 individuals. Group A was the control group (not infected) group B (infected with C. jejuni ATCC 33291), and group C (infected with field isolate of C. jejuni/C1). Infection of the chicken is done 0.5 ml peroral suspension concentration of104cfu/ml. Anova Duncan is used to analyze parameters of body weight, increase weight gain, feed consumption, FCR values. Kurskall Walis method used to analyze the parameters non-parametric form of the score changes in the macroscopic and microscopic intestinal and liver. Infection of C. jejuni changes the pathology anatomy of intestine i.e. hyperemia, enteritis and enteritis catharalis haemorrhagic. A microscopic change of intestinal is oedema,haemorrhage and infiltration of inflammatory cell. Changes of pathology anatomy liver are colour smeary, congesti, pale, fragile and necrotic. Microscopic changes of liver are degeneration and focal hepatic necrosis. Group observation infected by C. jejuni caused chicken cannot reach maximum body weight and can be detrimental to farmers because of increase of the value of the feed conversion ratio (FCR).